Microreactors in preparative chemistry : practical aspects in bioprocessing, nanotechnology, catalysis and more - Reschetilowski, Wladimir (Weinheim, Germany : Wiley-VCH, 2013)
This is the first book in the field to focus on these aspects, providing extremely valuable information unavailable elsewhere for anyone seeking the practical application of microreactor technology in preparative chemistry. The topics covered branch out in three different directions. To begin with, the knowledge necessary for the preparative chemistry concerning the influence of the so-called microeffects on the reaction procedure and on mass and heat transfer as well as the surface phenomena are provided in detail. Next, practical aspects of the synthesis of various basic chemicals and fi.
4.4.4 Determination of Amino Acids in Goods and Foods4.5 Microenzyme Membrane Reactor/Micromembrane Chromatography; 4.6 Nucleic Acid Analysis in Microchannels; 4.7 Saccharide Analyses in Microdevices; 4.8 Practical Exercise: Lipase-Catalyzed Esterification Reaction; References; 5 Bioprocessing in Microreactors; 5.1 Introduction; 5.2 Background; 5.2.1 Basic Elements of a Biosensor; 5.2.2 Different Sensing Methods; 5.2.3 The Effect of Reducing Dimensionality and Length Scales of Biosensors; 5.2.4 Biosensors Based on Field-Effect Transistors; 5.2.4.1 The Main Working Principle of FET Sensors.
Edition statement from running title area.
Includes bibliographical references and index.
Print version record.
Keywords: Microreactors; Chemistry; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Chemistry; Microreactors; Electronic books